Impacto Econômico da erosão na praia do Hermenegildo (RS), Brasil. - ESTEVES, LUCIANA SLOMP; DOS SANTOS, ISAAC RODRIGUES (Pesquisas em Geociências, 2001)
Although there is still a discussion about the extent of erosion along the Rio Grande do Sul shoreline, some places are recognized as intensely eroded, such as Jardim do Éden beach, Conceição Lighthouse, and Hermenegildo. This study evaluates the economic impacts of erosion in Hermenegildo based on the costs of coastal protection, destruction of structures during storms, and depreciation of beachfront property values. The study area consists in the 2-km long urbanized shore of Hermenegildo, a beach village located in the southernmost littoral of Brazil, 12 km north of the Uruguayan border. Erosion has threatened beachfront development during storms, resulting in a heavily armored shoreline. Quarrystone revetments (rip rap) and/or seawalls are the most common structures. A strong storm struck this coast in 16 April 1999 destructing 22 houses, all concrete structures, half of the quarrystone revetments, and 80% of the timber seawalls. After that storm, similar structures were built to protect beachfront properties. According to interviews conducted with property owners, average protection costs were estimated in U$ 2,203/property or U$79,308/km. Extrapolating the average costs for the 72 protected properties, total expenses in coastal defense is estimated in U$ 158,616. Considering a storm with same intensity and destruction power reaching the coast of Hermenegildo, the expected damage in land loss, destruction of houses and structures would be in the order of U$ 394,000. Analysis of the real estate sales in the last three years indicates a depreciation of 50-80% in beachfront property values while properties located further inland had a depreciation of 10%. Beach erosion has impacted the local economy and will continue to do so until the problem is effectively addressed. As the values at risk in Hermenegildo are relatively lower than usual coastal protection measures, probably relocation of structures or alternative techniques might be the best management option.